Computer games : text, narrative and play. - Carr, Diane, ....-; Buckingham, David, 1954-; Burn, Andrew, ....- (Cambridge : Polity, 2006)
Computer games are one of the most exciting and rapidly evolving media of our time. Revenues from console and computer games have now overtaken those from Hollywood movies; and online gaming is one of the fastest-growing areas of the internet. Games are no longer just kids' stuff: the majority of players are now adults, and the market is constantly broadening. The visual style of games has become increasingly sophisticated, and the complexities of game-play are ever more challenging. Meanwhile, the iconography and generic forms of games are increasingly influencing a whole range of other media, from films and television to books and toys. This book provides a systematic, comprehensive introduction to the analysis of computer and video games. It introduces key concepts and approaches drawn from literary, film and media theory in an accessible and concrete manner; and it tests their use and relevance by applying them to a small but representative selection of role-playing and action-adventure games. It combines methods of textual analysis and audience research, showing how the combination of such methods can give a more complete picture of these playable texts and the fan cultures they generate. Clearly written and engaging, it will be a key text for students in the field and for all those with an interest in taking games seriously